Trichinella spiralis Secreted Enzymes Regulate Nucleotide-Induced Mast Cell Activation and Release of Mouse Mast Cell Protease 1 - Afferson, Holly C. (American Society for Microbiology, 2012)
Extracellular nucleotides are important triggers of innate immunity, acting on a wide variety of cells via signaling through purinergic receptors. Mucosal mast cells contribute to expulsion of a number of gastrointestinal nematode parasites, and mouse mast cell protease 1 has been shown to have a critical role in clearance of Trichinella spiralis from the intestinal tract. We show here that adenosine, ADP, ATP, UDP, and UTP all stimulate calcium mobilization in bone marrow-derived mast cells with a mucosal phenotype. Secreted proteins from T. spiralis infective larvae inhibit nucleotide-induced mast cell activation, and that induced by ADP and UDP is specifically blocked by parasite secretory 5′-nucleotidase. Release of mouse mast cell protease 1 is stimulated by ADP and ATP. Both parasite secreted products and the 5′-nucleotidase inhibit ADP-induced release of mast cell protease, whereas that stimulated by ATP is partially inhibited by secreted products alone. This indicates that the 5′-nucleotidase contributes to but is not solely responsible for inhibition of nucleotide-mediated effects on mast cell function. Secretion of nucleotide-metabolizing enzymes by parasitic nematodes most likely evolved as a strategy for suppression of innate immune responses and is discussed in this context.